PEMIKIRAN MUHAMMAD NATSIR MENGENAI DEMOKRASI TEISTIK SERTA RELEVANSINYA DENGAN DEMOKRASI DI INDONESIA SAAT INI - Mahrub, Yan Khairil; ., Yuwanto; Abdulrahman, Wahid (Journal of Politic and Government Studies, 2017)
Nowadays democracy practice in Indonesia is an important concern in society, democracy becomes an interesting discussion to be studied, Indonesia is a pluralistic country that majority of people embrace Islam, it becomes a background which bring up a concept of religious democracy which once in by a figure of Indonesian Islamic thinker Muhammad Natsir. In particular, the writer will raise the idea of democracy offered by an intellectual, a man, and a politician, Mohammad Natsir. Muhammad Natsir is a modernist who leads the largest Islamic party in Indonesia, Masyumi, he believes with Islam being made a basis for his running democracy will be able to control the sustainability of democracy. This research model is literature research using beberepa method that is, descriptive method of history, interpretation, and induction. The results of this study show that theistic Democracy is a concept of Muhammad Natsir who said Islam as a religion, must be a tool of control in running a democracy, in the mind of Muhammad Natsir, religion as an important instrument in the formation of democracy in this case Islam, Natsir believes a democracy in which it abandoned the element of religion or could also be called secularism would be capable of destroying a State itself. In the writer's view when Islam as the basis of the state applied today will surely be experiencing distress and irrelevant to the state of Indonesia. However, the Islamic concept offered by Natsir is relevant for the life of Indonesian society. It can be concluded that Indonesia can not accept Islam as the basis of the state, but Indonesia can accept Islamic values to enter the country with Pancasila as the basis of the country.Keywords : Theistic Democracy, Indonesian Democracy, Relevance